1999
DOI: 10.1002/(sici)1097-461x(1999)73:2<209::aid-qua14>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics studies of a synthetic biomimetic model of galactose oxidase

Abstract: Very recently, highly efficient biomimetic models of the mononuclear copper enzyme galactose oxidase were synthesized which are able to reproduce the structural, spectroscopic, and functional properties of the native system exceptionally well. We have characterized an inactive and an active form of one of these biomimetic compounds using unrestricted dynamical density functional calculations. The peculiar nonsquare planar O N -coordination geometry of the copper ion in the catalytically 2 2 Ž . inactive EPR-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…This behavior is consistent with previous theoretical findings for other biological Cu(II) complexes, which were suggested as an indication of the strong Coulombic repulsion between the electron in the formally d 9 ion 57, 58. By a closer inspection of the α‐ and β‐orbital levels, one notes that the α orbitals of copper are more stabilized than the corresponding β ones.…”
Section: Resultssupporting
confidence: 91%
“…This behavior is consistent with previous theoretical findings for other biological Cu(II) complexes, which were suggested as an indication of the strong Coulombic repulsion between the electron in the formally d 9 ion 57, 58. By a closer inspection of the α‐ and β‐orbital levels, one notes that the α orbitals of copper are more stabilized than the corresponding β ones.…”
Section: Resultssupporting
confidence: 91%
“… Proposed mechanisms for the catalytic oxidation of alcohols by [Cu(L 12 · )] (A), and simplified models of [Cu(L 2 )] (B) and [Cu(L 54 )] (C) [adapted from ref 46. (A), ref 102,103. (B) and ref 104.…”
Section: Modeling the Properties Of The Go Active Sitementioning
confidence: 99%
“…Theoretical approaches to the oxidation of methoxide by [Cu(L 2 · )]102,103 and [Cu(L 54 · )]104 (in their Cu II ‐phenoxyl radical form) have been undertaken. Ab initio molecular dynamics studies on [Cu(L 2 · )] have shown that the methoxide adduct is a five‐coordinate distorted pyramidal phenoxylcopper(II) complex 102,103. The methoxide binds in the equatorial plane with a short Cu–O bond (1.93 Å), whereas the phenoxyl becomes an axial ligand with a much longer Cu–O bond (2.54 Å).…”
Section: Modeling the Properties Of The Go Active Sitementioning
confidence: 99%
“…A number of recent quantum‐chemical investigations have aimed at a full atomistic characterization of the enzymatic reaction mechanism, thereby complementing the available experimental data 1619. We have recently performed a mechanistic analysis of the functional biomimetic compound developed by Wang et al4 (MIM0 in Scheme )18 in direct comparison with its natural target 17. This study identified the delocalization of the unpaired spin density during the rate‐determining H‐abstraction step (Scheme , C → D ) as the crucial determinant for the efficiency of the process.…”
Section: Methodsmentioning
confidence: 99%
“…23 Geometries were converged up to a residual nuclear gradient of 0.001 atomic units. In CPMD calculations, the Kohn–Sham orbitals were expanded in plane waves with an energy cutoff of 80 Ry, which has been shown to be sufficiently accurate for these compounds 17. In ADF calculations we used DZP (H, N, O) and TZP (Cu, Ti, Ru, Rh, Pd) basis sets.…”
Section: Methodsmentioning
confidence: 99%